Mangiferin Prevents TBHP-Induced Apoptosis and ECM Degradation in Mouse Osteoarthritic Chondrocytes via Restoring Autophagy and Ameliorates Murine Osteoarthritis. (15th October 2019) - Li, Yao; Wu, Yaosen; Jiang, Kaixia; Han, Wen; Zhang, Jing; Xie, Lin; Liu, Yanlong; Xiao, Jian; Wang, Xiangyang
Abstract : Osteoarthritis (OA) is an age-related degenerative disease with complicated pathology involving chondrocyte apoptosis and extracellular matrix (ECM) degradation. Previous studies have shown that moderate autophagy has a protective effect against apoptosis in chondrocyte. Mangiferin is a natural polyphenol and exerts multiple pharmacological effects on different diseases in various preclinical studies. In this study, we investigated the effects of mangiferin on OA and delineated a potential molecular mechanism. In vitro, mangiferin treatment inhibited the expression of proapoptotic proteins induced by tert -butyl hydroperoxide (TBHP), increased the expression of antiapoptotic Bcl-2, and prevented ECM degradation by inhibiting the production of matrix-degrading enzyme. Mechanistically, mangiferin enhanced autophagy by activating the AMP-activated protein kinase (AMPK) signaling pathway. On the contrary, inhibition of autophagy partly abolished the protective effects of mangiferin on antiapoptosis and ECM synthesis in TBHP-treated chondrocyte. Correspondingly, the protective effect of mangiferin was also found in a mouse OA model. In conclusion, our results suggested that mangiferin serves as a potentially applicable candidate for treating OA.